Penguatan Kompetensi Guru dalam Penyusunan Pedoman Praktikum IPA SD untuk Melatih Berpikir Kritis Siswa di Sekolah Dasar Sakatiga Seberang Ogan Ilir - Suratmi Suratmi; Laihat Laihat; Aswasulasikin Aswasulasikin; Nurdin Kamil; Meilani Tirta Sari; Mazda Leva Okta Safitri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance teachers’ competencies in developing science practicum guidelines to foster elementary school students’ critical thinking skills. The program employed a Participatory Learning and Action (PLA) approach involving 20 elementary school teachers in Sakatiga, Seberang Ogan Ilir. Program evaluation was conducted using written tests (pre-tests and post-tests), observation sheets, interviews, and reflective discussions. The data were analyzed using descriptive quantitative methods. The results indicate a significant improvement in teachers’ competencies. The average pre-test scores were categorized as moderate, while post-test results improved to a very good category after teachers participated in the training and mentoring activities. In addition, the quality of the instructional products developed by the teachers also improved, and enhanced teacher competencies were reflected in classroom instructional practices. The impact on students was evidenced by increased active participation, enthusiasm, and confidence in asking questions and expressing opinions during science practicum activities.